2018
DOI: 10.4028/www.scientific.net/msf.924.389
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Ni-Al Ohmic Contacts to p-Type 4H-SiC Using Semi-Salicide Processing

Abstract: Most semiconductor devices require low-resistance ohmic contact to p-type doped regions. In this work, we present a semi-salicide process that forms low-resistance contacts (~10-4 Ω cm2) to epitaxially grown p-type (>5×1018 cm-3) 4H-SiC at temperatures as low as 600 °C using rapid thermal processing (RTP). The first step is to self-align the nickel silicide (Ni2Si) at 600 °C. The second step is to deposit aluminium on top of the silicide, pattern it and then perform a second annealing step in the range 500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The resistance of the ptype contacts decreased by higher SSA temperature, but it was still partially rectifying even at 1000 C. Even if the contacts become ohmic at a higher annealing temperature, the process is unlikely to be competitive with already established contact processes. 3,[28][29][30] As such, it was found that the selfaligned CoSi x is a poor candidate for low resistance ohmic contacts to p-type 4H-SiC. It is interesting to compare the result to that achieved by Lundberg and Ö stling.…”
Section: Electrical Characterizationmentioning
confidence: 95%
See 2 more Smart Citations
“…The resistance of the ptype contacts decreased by higher SSA temperature, but it was still partially rectifying even at 1000 C. Even if the contacts become ohmic at a higher annealing temperature, the process is unlikely to be competitive with already established contact processes. 3,[28][29][30] As such, it was found that the selfaligned CoSi x is a poor candidate for low resistance ohmic contacts to p-type 4H-SiC. It is interesting to compare the result to that achieved by Lundberg and Ö stling.…”
Section: Electrical Characterizationmentioning
confidence: 95%
“…An example of such a study was the finding that the self-aligned Ni 2 Si can be turned from rectifying to ohmic to p-type 4H-SiC by alloying it with aluminum at relatively low temperatures. 3 A comparison between self-aligned nickel silicide and lift-off process for power devices was recently presented by Sledziewski at the conference of silicon carbide and related materials (ECSCRM 2018). Nickel-based contact processes give good ohmic contacts to ntype 4H-SiC, 2,4,5 but often gives rectifying contacts to p-type, with some notable exceptions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The n-type ohmic contact was made by a Ni-based selfaligned two-step-annealing process [30]. The p-type Ohmic contact was made by a Ni-Al-based semi-self-aligned process [31]. The interconnect dielectric was PECVD oxide and the interconnect metal was sputtered TiW and Al.…”
Section: Design and Fabricationmentioning
confidence: 99%
“…As a result, a borderless contact (BLC) structure was adopted. BLC nitride was used as an etch stop layer and cobalt (Co) silicide [1] was applied to the salicide process [2].…”
Section: Introductionmentioning
confidence: 99%